2019
DOI: 10.1111/nph.16167
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome respiration pathway and sulphur metabolism sustain stress tolerance to low temperature in the Antarctic species Colobanthus quitensis

Abstract: Understanding the strategies employed by plant species that live in extreme environments offers the possibility to discover stress tolerance mechanisms. We studied the physiological, antioxidant and metabolic responses to three temperature conditions (4, 15, and 23°C) of Colobanthus quitensis (CQ), one of the only two native vascular species in Antarctica. We also employed Dianthus chinensis (DC), to assess the effects of the treatments in a non-Antarctic species from the same family.Using fused LASSO modellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 90 publications
(120 reference statements)
0
35
0
Order By: Relevance
“…Although summers in the Maritime Antarctic are less harsh than the rest of the Antarctic continent, air temperatures during the day are just slightly positive (Convey et al, ) and sub‐zero temperatures frequently occurred during the nights, particularly on King George Island (South Shetland; Sierra‐Almeida et al, ; Clemente‐Moreno, Omranian, et al, ). These constant low temperatures combined with extremely changing irradiance, poor soils, and cold dry winds make Antarctica one of the most extreme continent for terrestrial vegetation (Bramley‐Alves et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although summers in the Maritime Antarctic are less harsh than the rest of the Antarctic continent, air temperatures during the day are just slightly positive (Convey et al, ) and sub‐zero temperatures frequently occurred during the nights, particularly on King George Island (South Shetland; Sierra‐Almeida et al, ; Clemente‐Moreno, Omranian, et al, ). These constant low temperatures combined with extremely changing irradiance, poor soils, and cold dry winds make Antarctica one of the most extreme continent for terrestrial vegetation (Bramley‐Alves et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the Antarctic Peninsula, terrestrial vegetation is constrained to the scarce ice‐free areas, typically located along the coast and adjacent islands; this area is known as Maritime Antarctic (Convey, ), and it is characterized by a milder climate compared with the east of the continent at the same latitude (Bargagli, ). The maritime influence generates summer conditions with slightly positive temperatures during the day and also sub‐zero temperatures during the night (Clemente‐Moreno et al, ; Convey, Coulson, Worland, & Sjöblom, ; Sierra‐Almeida, Cavieres, & Bravo, ). Climate is also characterized by strong dry winds and extremely variable solar radiation (Bramley‐Alves, King, Robinson, & Miller, ; Cavieres et al, , and references therein).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same experiment, the authors pointed out that heat dissipation by the xanthophyll cycle allows C. quitensis to deal with the energy imbalance (Pérez‐Torres et al , , ). More recently, it was demonstrated that C. quitensis exhibits constitutively high antioxidant capacity that is mainly related to sulphur and secondary metabolism, with normal antioxidant enzyme activities (Clemente‐Moreno et al , ). Conversely, D. antarctica displays a rather unique pattern of antioxidant enzyme activities after long‐term exposure to low temperature.…”
Section: Primary Metabolism and Antioxidant Biochemistrymentioning
confidence: 99%
“…The only two native vascular plants of Antarctica (Figure c) have been extensively studied in terms of temperature, water availability and nutrient deficiency (Sáez et al , , ,b; Clemente‐Moreno et al , , ). Interestingly, for both species, g m is the most important limitation under low temperature, drought and nutrient deficiency, as has been previously reported for species from semiarid‐arid environments (Galmés et al , ).…”
Section: Photosynthesis In Extreme Environments: Taking Advantage Of mentioning
confidence: 99%